Corticosteroids combined with infliximab vs. corticosteroids sequential infliximab for acute severe ulcerative colitis with mucosal deficiency: a retrospective study - Liu, Xiaolei; Xue, Xianmin; Zhu, Xiaojing; Liu, Jun; Shi, Yongquan; Chen, Min (Frontiers in Medicine, 2024)
Introduction: Type of mucosa-deficiency is the most challenging condition in acute severe ulcerative colitis (ASUC) patients. Intravenous corticosteroids (CS) are the first-line treatment, infliximab (IFX) usually is used as the rescue therapy. But the efficacy remains unsatisfactory. We investigated whether CS combined IFX as first-line therapy improved the efficacy of ASUC patients with mucosa-deficiency.Methods: A retrospective study was performed at a tertiary inflammatory bowel disease center. The primary outcomes were clinical remission, endoscopic improvement and endoscopic remission at week 14. The Secondary outcomes included colectomy rate within 90 days and durable clinical remission.Results: A total of 43 ASUC patients with mucosa-deficiency were included for analysis (25 in CS combined IFX group and 18 in CS sequential IFX group). At week 14, endoscopic improvement was achieved in 21/25 (84.0%) receiving CS combined IFX regimen versus 9/18 (50.0%) receiving CS sequential IFX regimen (P=0.017). The durable clinical remission rates were significantly higher in the combined group than in the sequential group (85.7% vs 35.7%, P=0.004). No statistically significance was observed between the two groups on clinical and endoscopic remission at week 14, and colectomy rate within 90 days. Multivariate analysis confirmed CS combined IFX regimen was independent predictive factor for higher endoscopic improvement rate at week 14 (OR 8.428, 95%CI 1.539-46.153, P=0.014) and durable clinical remission rate (OR 10.800, 95%CI 2.095-55.666, P=0.004).Conclusions: CS combined IFX as the first-line therapy may be an effective induction strategy in ASUC patients with mucosa-deficiency. Further muti-center prospective study of large size is needed.